DEVELOPING STUDENTS’ LINGUISTIC THINKING WITH ARTIFICIAL INTELLIGENCE: A PSYCHOLINGUISTIC PERSPECTIVE - Odiljonova Kamola Abduvosit kizi (Bright Mind Publishing, 2025)
The integration of artificial intelligence (AI) into education has transformed approaches to developing students’ cognitive and linguistic capacities. Linguistic thinking, understood as the ability to comprehend, analyze, and generate meaning through language, represents a crucial component of intellectual development in higher education. From a psycholinguistic perspective, language and thought are deeply interconnected, as language constitutes the material form of thought and simultaneously mediates cognitive processes. This article explores the significance of employing AI-based technologies to enhance linguistic thinking, arguing that AI tools, when harmonized with psycholinguistic principles, create favorable conditions for fostering analytical, synthetic, and creative modes of reasoning in students.
Keywords: Artificial Intelligence; Linguistic Thinking; Psycholinguistics; Higher Education; Communicative Competence; Pedagogical Innovations; Digital Learning.